ChemInform Abstract: Inspired by Nature: The 3‐Halo‐4, 5‐dihydroisoxazole Moiety as a Novel Molecular Warhead for the Design of Covalent Inhibitors. Issue 9 (February 2016) - Pinto, Andrea; Tamborini, Lucia; Cullia, Gregorio; Conti, Paola; De Micheli, Carlo
Abstract: Review: [30 refs.